Mycotic and Bacterial Infections - Duldulao, Phillip M.; Ortega, Adrián E.; Delgadillo, Xavier (Clinics in Colon and Rectal Surgery, 2019)
This article reviews the salient clinical features, evaluation, and treatment of mycotic and bacterial infections of the perianal and contiguous zones of the human body.
Keywords: mycotic; bacterial; fungal; tinea; candidiasis; erythrasma; impetigo; erysipelas; streptococcal; Staphylococcus; mycobacterial; actinomycosis